The Effect of Giving Tofu Dregs and Manure on The Growth of Pakcoy (Brassica rapa subsp. chinensis) Plants - Juni Artika; Marjanah; Siska Rita Mahyuny (Jurnal Biologi Tropis, 2023)
Pakcoy is a variety of mustard greens whose leaves are used as a vegetable. Pakcoy mustard greens are also often called spoon mustard greens because their shape resembles a spoon. The aim of this research was to determine which factors and chemical combinations had the greatest influence on the growth of pak choy (Brassica rapa subsp. chinensis) plants. Experimental methodology was used in this research's quantitative approach. There were 24 samples used in this research experiment, which included 6 treatments and 4 replications. Statistical analysis of variance (ANOVA) test was used in data analysis for this study. The hypothesis testing process then continues using data from the prerequisite tests, namely ordinariness test and homogeneity test. The results showed that tofu dregs and manure had no effect on the total fresh weight of harvested plants, but did affect plant height and number of leaves at 2 WAP and 6 WAP observations.including the addition of soil and manure, has the best composition for growth in plant height and wet weight of the entire crop.The combination of soil, tofu dregs and manure is a good treatment for increasing the number of leaves.The plant height parameter observed at 2 WAP and 4 WAP in treatments P3 and P1 was the as it were parameter that was altogether diverse between each treatment, based on the findings of the BNT test.